Odpowiedzi

2010-03-24T16:28:46+01:00
A) 12y - ( y + 5 ) = 10y - 1
12y - y -5 = 10y -1
12y - 10y - y = -1 +5
y=4

b) 2(u - 5 ) +15 = 3 ( u - 4 ) + 4
2u -10 +15 = 3u -12 +4
2u - 3u = -12 +4 +10 -15
-u = - 13
u = 13

c) -3( y/3 +1 ) - 2 = 4 (1 - y )
-3y/3 -3 -2 =4 -4y
-y +4y = 4+3 +2
3y = 9 /:3
y= 3

d) 2(3a - 2 ) - 6 = 4,5 ( 2a - 1 ) +½
6a -4 -6 = 9a - 4,5 +½
6a - 9a = -4,5 +½ +4 +6
-3a = 6 /:(-3)
a = -2

liczę na naj :)
1 5 1
2010-03-24T16:30:10+01:00
A) 12y - ( y + 5 ) = 10y - 1
12y-y-5=10y-1
11y-10y=-1+5
y=4
b) 2(u - 5 ) +15 = 3 ( u - 4 ) + 4
2u-10+15=3u-12+4
2u-3u=-12+4+10-15
-u=-13/:(-1)
u=13
c) -3( y/3 +1 ) - 2 = 4 (1 - y )
-y-3-2=4-4y
-y+4y=4+3+2
3y=9/:3
y=3
d) 2(3a - 2 ) - 6 = 4,5 ( 2a - 1 ) +½
6a-4-6=9a-4,5+0,5
6a-9a=-4,5+0,5+4+6
-3a=6/:(-3)
a=-2